Eight‐channel hybrid‐integrated laser array with 100 GHz channel spacing. Issue 20 (26th August 2020) - Wang, Mingjin; Dong, Fengxin; Meng, Ranzhe; Ma, Pijie; Liu, Jing; Wang, Hailing; Wang, Xueyou; Zheng, Wanhua
Abstract : An eight‐channel hybrid‐integrated light source with 100 GHz channel spacing fabricated by a passive alignment technology is demonstrated. Side mode suppression ratios of better than 40 dB were obtained via grating couplers under eight‐channel simultaneous operation at a continuous wave current of 600 mA and 25°C. The surface slotted laser array fabricated by standard lithography butt‐joint with silicon photonic devices was demonstrated for the first time, to the best of the authors' knowledge.